The Evolving Economic Relationship Between the United States and Japan and its Influence on "Comfort Women" Peacemaking Efforts - Park, Ellen Y. (Tufts University. Tisch Library., 2019)
Tisch Library Undergraduate Research Award Winner, 2019; "Comfort women" is a euphemism used to name the 100,000 - 200,000 Asian women (mainly of Korean descent) who were forced into sexual slavery by the Japanese Imperial Army before and during the Second World War. This paper focuses on the history of "comfort women" and the evolving economic relationship between the United States and Japan its impact on "comfort women" peacemaking efforts throughout the past three decades. It is concluded that while not the only factor, international economic relationships played a significant role in the United States' stance on resolving the issue of "comfort women".